The adoration of Jenna Fox - Pearson, Mary (Mary E.) (Square Fish, 2009)
Seventeen-year-old Jenna Angeline Fox wakes from a long coma with no memory of who she is, and is sent home with her mother and inexplicably hostile grandmother where hours of video recordings of her childhood help spark her memories and send her on a horrifying quest to learn what really happened to her.